A prática contemporânea de tradução com auxílio de sistemas de memórias e os limites da responsabilidade do tradutor - Stupiello, Erika Nogueira de Andrade [UNESP] (2012)
This paper analyzes the growing adoption of translation tools by the contemporary translator working for markets such as the localization industry. The fast turnaround pace of translation of electronic texts ends up conditioning the employment of translators to their ability to use the resources provided by tools such as translation memories systems efficiently. These systems, as envisioned in their early conception, would allow users to increase productivity and, simultaneously, standardize their terminological production. Seeking to go beyond the predominantly descriptive approaches of these tools, some theoretical assumptions upholding the use of translation memories are examined. From this perspective, the translator’s involvement with the work in progress is analyzed, mainly when this professional is part of a larger process of production and distribution of information by electronic means and for diverse audiences. Ultimately, the consequences of the employment of these tools are taken into consideration, such as those between translator/translation and translator/client, as well as the extension of the responsibility of the translator dedicated to developing partially automated translations.